High sustained viral response rate in patients with hepatitis C using generic sofosbuvir and daclatasvir in Phnom Penh, Cambodia. Issue 9 (23rd July 2020) - Zhang, Meiwen; O'Keefe, Daniel; Iwamoto, Momoko; Sann, Kimchamroeun; Kien, Antharo; Hang, Vithurneat; Brucker, Cecile; Jolivet, Pascal; Ly, Sovann; Chhit, Dimanche; Balkan, Suna; Marquardt, Tonia; et al.
Abstract: Safe and efficacious pan‐genotypic direct‐acting antiviral (DAA) regimens, such as sofosbuvir and daclatasvir (SOF + DCV), facilitate simplified models of care for hepatitis C virus (HCV). However, in Cambodia access to HCV testing and treatment has typically been low. In response, Médecins Sans Frontières (MSF) implemented a HCV testing and treatment pilot project in Phnom Penh, Cambodia in 2016. This project provides the first real‐world evidence of SOF + DCV effectiveness across a large patient cohort using a simplified care model in Cambodia. Patients treated with SOF + DCV from September 2016 to June 2019 were included in the analysis. Medical standard operational procedures (SOPs) were simplified significantly across the study period. Treatment effectiveness was assessed by sustained viral response at 12 weeks post‐treatment (SVR12) according to a modified intention‐to‐treat methodology. Treatment safety was assessed by clinical outcome and occurrence of serious and nonserious adverse events (S/AE). Of 9158 patients, median age was 57 years and 39.6% were male. At baseline assessment, 27.2% of patients had compensated cirrhosis and 2.9% had decompensated cirrhosis. Genotype 6 was predominant (53.0%). Among patients analysed according to modified intention to treat (n = 8525), treatment effectiveness was high, with 97.2% of patients achieving SVR12. Occurrence of SAE was low (0.7%). Treatment effectiveness and safety was not affected by the iterative simplification to treatment modality. In conclusion, in this large treatment cohort in Phnom Penh, Cambodia, the SOF + DCV regimen showed high rates of treatment effectiveness and safety across patient sub‐groups and during progressive simplification.